Windows Server 2019: Advanced Networking Features. - McMillen, Robert (linkedin.com, 2019)
Learn about the advanced networking features of Windows Server 2019. Explore Software Defined Networking (SDN), high-performance interfaces, Kubernetes, Azure, and more.